Predictors of cerebral embolisation after percutaneous transfemoral aortic valve implantation (TAVI) in the RETORIC substudy. (25th November 2020) - Suhai, F; Varga, A; Nagy, A.I; Apor, A; Panajotu, A; Szilveszter, B; Bartykowszki, A; Karady, J; Merkely, B; Maurovich-Horvat, P
Abstract: Purpose: To evaluate the predictors, occurrence and distribution of TAVI-related silent ischemic brain lesions using diffusion MRI. Methods and materials: We investigated 109 consecutive patients with severe aortic stenosis from the prospective arm of the RETORIC study who underwent brain MRI one week afterpercutaneous transfemoral aortic valve implantation TAVI. To determine the occurrence and distribution of periprocedural cerebral ischemic lesions averaged diffusion-weighted images (trace) and mean diffusivity (MD) maps from the DTI dataset were used. To evaluate the aortic valve calcium score (AVCS), we assessed the preoperative prospectively ECG-triggered cardiac CT (256-slice MDCT). We also assessed the periprocedural factors such as periprocedural time, pre- and postdilatation. Multivariate linear regression analysis was performed to identify the independent predictors of TAVI-related ischemic lesions. Results: After TAVI, a total of 918 new cerebral ischemic lesions were detected in 100/109 patients (92%). The median ischemic lesion volume was 237 μl (interquartile range 89.5–650) with a median lesion number of 6 (2–10) per patient. 759/918 lesions (83%) were supratentorial (389 left vs 370 right). Most lesions (628/918, 68%) were subcortical; the left and right MCA territories were the most affected (190. The vast majority of ischemic lesions were clinically silent (96%); 4% of patients had stroke which was proven by MRI. The median AVCS was 2769 (interquartile range 1858–4537). Balloon predilatation during TAVI procedure showed significant correlation with increased total ischemic lesion volume (p<0.001, β = 0.370) on univariate analysis, AVCS, periprocedural time, or postdilatation were not associated with ischemic load on MRI (p<0.05). Conclusions: Periprocedural ischemic lesions are frequent (92%), most of them are clinically silent, however. Only balloon dilatation during TAVI was a predictor of increased ischemic load. Funding Acknowledgement: Type of funding source: None